Radio over fiber system based on a hybrid link for next generation of optical fiber communication - Kaoutar Saidi Alaoui; J. Foshi; Y. Zouine (Institute of Advanced Engineering and Science, 2019)
Radio over fiber technology will play an important role in solving problems facing wireless technology. Envisaging a global village, people could transmit and receive “anytime, anywhere, and anything”. In addition, the explosive growth in internet applications such as the World Wide Web, demonstrates the tremendous increase in bandwidth and low power that the coming world of multimedia interactive applications will require from future networks. ROF technology uses multicarrier modulation like orthogonal frequency division multiplexing (OFDM), which provides an opportunity of having an increased in bandwidth together with an affordable cost and this idea has recently become a suitable topic for many research works. On the other hand, SAC-OCDMA (Spectral Amplitude Coding Optical Code Division Multiple Access) technique is able to enhance the data rate of system and increase the number of user. In this paper we introduce a ROF link using a hybrid OFDM/SAC-OCDMA technique.